2005
DOI: 10.1002/j.2161-007x.2005.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapists' Use of Religious and Spiritual Interventions in Christian Counseling: A Preliminary Report

Abstract: Thi s study explored the use of religious and spiritual interventions in counseling by Christian therapists ( N = 100). Use of religious and spiritual interventions correlated with personal religiousness and clinical training involving religious clients and religious and spiritual interventions. Course work involving either psychology or theology did not correlate with use of or self-reported competency in using religious and spiritual interventions. Self-reported competency was associated with personal religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 15 publications
2
34
1
2
Order By: Relevance
“…There are very few empirical studies on the impact of counselors' religious or spiritual beliefs on their counseling work. Research with Christian counselors primarily addresses the use of religious and spiritual interventions in therapy (Walker, Gorsuch, & Tan, 2005) and the integration of religious beliefs with professional ethics (Evans, 2003). Beutler et al (2004) discussed how this gap in the research prevents counselors from obtaining an understanding of ways religious influences may be changing in psychotherapy.…”
Section: Religion and Spiritualitymentioning
confidence: 99%
“…There are very few empirical studies on the impact of counselors' religious or spiritual beliefs on their counseling work. Research with Christian counselors primarily addresses the use of religious and spiritual interventions in therapy (Walker, Gorsuch, & Tan, 2005) and the integration of religious beliefs with professional ethics (Evans, 2003). Beutler et al (2004) discussed how this gap in the research prevents counselors from obtaining an understanding of ways religious influences may be changing in psychotherapy.…”
Section: Religion and Spiritualitymentioning
confidence: 99%
“…Clients seeking counseling services often want to integrate their spiritual or religious worldviews into treatment (Aten & Hernandez, ; Worthington & Sandage, ). Counselors who subscribe to a spiritual or religious worldview tend to be more open to implementing spiritual or religious interventions in counseling (Walker, Gorsuch, & Tan, ). However, these same clinicians often avoid implementing spiritual interventions or treatments in counseling because of the lack of evidence validating such modalities in clinical settings (Walker et al, ).…”
Section: Competency Content Area 6: Diagnosis and Treatmentmentioning
confidence: 99%
“…There is also a tendency, however, for professionals to adhere to their own spirituality when choosing the application of spiritual interventions and technique with clients, as research has shown (Crisp, 2010;Sheridan, 2009;Walker, Gorsuch & Tan, 2005;Mattison, Jayaratne & Croxton, 2000). This fact may place the therapeutic relationship in unequal power dynamics that favor the service provider (Vargas & Wilson 2011;Blow, Sprenkle, & Davis, 2007).…”
Section: The Case For Worldview-as-life-disposition Pedagogy In Sociamentioning
confidence: 99%